(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
The present paper provides new solution of Einstein’s field equations for the interior Metric of a fluid sphere with and without cosmological constant and by taking suitable conditions on g44. Various physical parameters have been found and discussed.